2005
DOI: 10.1002/jsfa.2275
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal treatments of two cowpea (Vigna unguiculata L. Walp) varieties: effect of micronisation on physicochemical and structural characteristics

Abstract: The effects of a hydrothermal treatment consisting of tempering (to 41% moisture) and heating to 153 • C (micronisation) on the structural and physicochemical characteristics of two cowpea varieties were studied. The untreated varieties had similar cooking times, although cooked Bechuana white cowpeas were significantly (P ≤ 0.05) softer and had a higher incidence of splitting than Var. 462 cowpeas. This may be due in part to differences in cotyledon structure affecting water uptake during cooking. The hydroth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(78 citation statements)
references
References 29 publications
6
72
0
Order By: Relevance
“…462 and Bechuana white) was explored by Mwangwela et al [32]. The cowpeas were micronized using a table-top micronizer in a single layer for 6 min to a final surface temperature of 153°C.…”
Section: Micronization Of Legumesmentioning
confidence: 99%
“…462 and Bechuana white) was explored by Mwangwela et al [32]. The cowpeas were micronized using a table-top micronizer in a single layer for 6 min to a final surface temperature of 153°C.…”
Section: Micronization Of Legumesmentioning
confidence: 99%
“…In other studies, it has been reported that seeds might crack and become tough with improved absorption, but might also suffer higher leaching losses, if were heated to a high temperature (above 140°C) using an infrared treatment (Abdul-Kadir, Bargman, & Rupnow, 1990;Fasina, Tyler, Pickard, Zheng, & Wang, 2001;Mwangwela, Waniska, & Minnaar, 2006). Variations in hydration and dehydration of soybean and safflower have been shown to be a function of relative humidity (Vijay, Dadlani, & Nagarajan, 2009).…”
Section: Introductionmentioning
confidence: 95%
“…One of the ways to minimize these changes is through adopting high‐temperature short time processing techniques (HTST). In the recent past, micronization, an HTST technique that utilizes near‐infrared (NIR) rays has been employed to process cereals and legumes, such as lentils, cowpeas, peas, beans, sorghum, barley, wheat, maize, and rice bran to shorten the cooking time, to improve nutritional value, as well as to inactivate enzymes and anti‐nutritional factors (Andrejko, Rydzak, Oelaska‐Grzywna, Goÿdziewska, & Kobus, ; Arntfield et al, ; Cruzy Celis, Rooney, & Mcdonough, ; Deepa & Hebbar, ; Emami, Meda, Pickard, & Tyler, ; Fasina, Tyler, Pickard, & Zheng et al, , Fasina, Tyler, Pickard, Zheng, & Wang, ; Mwangwela, Waniska, & Minnaar, ; Yilmaz, Tuncel, & Kocabiyik, ; Žilić et al, ). Research reports available on micronization of maize grains mainly focused on evaluating the effect of IR processing on nutritional properties, antioxidant activity and on fromation of maillard reaction products (Žilić et al, ; Žilić et al, ).…”
Section: Introductionmentioning
confidence: 99%